Skeletal and Cardiac Rhabdomyolysis in a Live-Stranded Neonatal Bryde's Whale With Fetal Distress - Câmara, Nakita; Sierra, Eva; Fernández, Antonio; Suárez-Santana, Cristian Manuel; Puig-Lozano, Raquel; Arbelo, Manuel; Herráez, Pedro (Frontiers in Veterinary Science, 2019)
The main objective of wildlife forensic investigation is to recognize pathologic changes and cause of death. Even though it may not always be possible to determine the specific illness and/or etiology, the description and subsequent interpretation of the injuries provide an invaluable understanding of pathology in cetacean post-mortem investigations. Although pathological studies have been previously reported in various cetacean species, such descriptions of the infraorder Mysticeti remain rare. A live-stranded neonatal Bryde’s whale (Balaenoptera edeni) which subsequently died soon after the stranding, was assessed by physical exam, blood examination, gross necropsy evaluation, histopathology and immunohistochemistry. It presented with elevated serum levels of creatine kinase, cardiac troponin I, urea, and creatinine. Microscopically, we observed keratin spicules (squamous epithelial cells) and areas of atelectasis in the lungs. Acute degeneration in the myocytes and cardiomyocytes were comparable to the findings previously described in cases of capture myopathy in live-stranded cetaceans. Immunohistochemistry biomarkers such as myoglobin, fibrinogen, and troponin were analyzed. Skeletal and myocardial damage has been documented in several cetacean species. However, this is the first reported case of skeletal and cardiac rhabdomyolysis associated with live-stranding in a newborn Bryde's whale that suffered from fetal distress.